MESSENGER observations of multiscale Kelvin‐Helmholtz vortices at Mercury. Issue 6 (4th June 2015) - Gershman, Daniel J.; Raines, Jim M.; Slavin, James A.; Zurbuchen, Thomas H.; Sundberg, Torbjörn; Boardsen, Scott A.; Anderson, Brian J.; Korth, Haje; Solomon, Sean C.
Abstract: Observations by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft in Mercury's magnetotail demonstrate for the first time that Na + ions exert a dynamic influence on Mercury's magnetospheric system. Na + ions are shown to contribute up to ~30% of the ion thermal pressure required to achieve pressure balance in the premidnight plasma sheet. High concentrations of planetary ions should lead to Na + dominance of the plasma mass density in these regions. On orbits with northward‐oriented interplanetary magnetic field and high (i.e., >1 cm −3 ) Na + concentrations, MESSENGER has often recorded magnetic field fluctuations near the Na + gyrofrequency associated with the Kelvin‐Helmholtz (K‐H) instability. These nightside K‐H vortices are characteristically different from those observed on Mercury's dayside that have a nearly constant wave frequency of ~0.025 Hz. Collectively, these observations suggest that large spatial gradients in the hot planetary ion population at Mercury may result in a transition from a fluid description to a kinetic description of vortex formation across the dusk terminator, providing the first set of truly multiscale observations of the K‐H instability at any of the diverse magnetospheric environments explored in the solar system. Key Points: Na + can contribute up to ~30% of Mercury's plasma sheet thermal pressure K‐H wave frequencies can correlate with the local Na + gyrofrequency K‐H at Mercury transitions from MHD to kinetic scale across the dusk terminator